2016
DOI: 10.1080/17512433.2017.1246179
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of pharmacokinetic variability of first-line anti-TB drugs

Abstract: Inter-individual variations in the pharmacokinetics (PK) of anti-TB drugs are known to occur, which could have important therapeutic implications in patient management. Areas covered: We compiled factors responsible for PK variability of anti-TB drugs reported from different settings that would give a better understanding about the challenges of PK variability of anti-TB medications. We searched PubMed data base and Google scholar from 1976 to the present using the key words 'Pharmacokinetics', 'pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 115 publications
1
13
0
Order By: Relevance
“…The development of cancer biology and drug discovery has identified thousands of therapeutics, many of which unfortunately failed to further develop into clinical drugs because of unfavorable druggability, such as poor solubility, low-membrane permeability, and instability in biological fluids. Meanwhile, the PK variations among different drugs would result in unwanted toxicity and variable therapeutic effects 26 , 27 . On this account, NMs have been demonstrated with the capacities of improving drug solubility and stability, as well as promoting the penetration through various biological barriers.…”
Section: Nanotechnology-based Codeliverymentioning
confidence: 99%
“…The development of cancer biology and drug discovery has identified thousands of therapeutics, many of which unfortunately failed to further develop into clinical drugs because of unfavorable druggability, such as poor solubility, low-membrane permeability, and instability in biological fluids. Meanwhile, the PK variations among different drugs would result in unwanted toxicity and variable therapeutic effects 26 , 27 . On this account, NMs have been demonstrated with the capacities of improving drug solubility and stability, as well as promoting the penetration through various biological barriers.…”
Section: Nanotechnology-based Codeliverymentioning
confidence: 99%
“…The recommended regimen consists of a 2-month intensive phase with all four FLDs, and a 4-month continuation phase with RIF and INH only [7]. Despite the utilization of weight-banded dosing, high pharmacokinetic (PK) variability has been reported for the FLDs in studies investigating the PK of these drugs [8][9][10]. The hollow-fibre infection model and murine model conducted with the four FLDs showed that their effectiveness is best reflected by the area under the concentration-time curve (AUC)/minimum inhibitory concentration (MIC) ratio [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in our TB patients treated under direct observation (DOT), moxifloxacin PK variability in plasma was found to be ninefold on 400 mg/day [ 36 ]. The PK of all anti-tuberculosis drugs could be affected by TB disease activity (wasting, loss of lean body mass, fat and serum proteins), HIV, diabetes or drug–drug interactions [ 37 , 38 ]. The PK interaction between rifampicin and moxifloxacin is well known [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%